IMPLEMENTASI SISTEM MANAJEMEN LOGISTIK OBAT DI RUMAH SAKIT MITRA SEHAT MANDIRI SIDOARJO`: `IMPLEMENTATION OF A MEDICATION LOGISTICS MANAGEMENT SYSTEM AT MITRA SEHAT MANDIRI HOSPITAL SIDOARJO - Priyoherianto, Andri; Iswandi, Iswandi; Fitriany, Erna; Budi L, Deny (JFL : Jurnal Farmasi Lampung, 2025)
The increased availability of medications today has led to a rise in demand for medical services. Drug logistics management in hospitals involves interrelated stages such as planning, procurement, storage, distribution, processing, evaluation, and monitoring. All of these stages require good coordination to function optimally. This study aims to examine the implementation of drug logistics management at the Pharmacy Installation of Mitra Sehat Mandiri Hospital in Sidoarjo using a qualitative descriptive approach with a cross-sectional design. The results show that training has a positive impact on employee performance, particularly in the input component. Adequate budgeting is necessary for purchasing medications and maintaining storage facilities and related equipment. Equipment must meet standards, have proper lighting, and be regularly calibrated. In general, the hospital’s logistics process includes planning through to supervision. Most medications are available as needed, although some may occasionally be out of stock due to supply shortages from distributors. Additionally, some damaged or expired drugs were found, indicating the need for a comprehensive evaluation of drug management to improve its effectiveness and efficiency. Overall, the availability of medications at this hospital is considered to be in accordance with demand. Keywords: Pharmacy Installation, Input and output components, Drug availability, Health services